Aging and the life course : - Quadagno, Jill S. (McGraw-Hill, 2005)
In writing this first edition text, Jill Quadagno's goal was to provide a comprehensive and contemporary view of the sociology of aging. She achieved her objective in the following ways: (1) hers is the first social gerontology text to take a life course approach, which stipulates that the quality of one's life in old age is the product of earlier choices, opportunities, and constraints; (2) her book highlights current public policy issues pertaining to aging; and (3) her book integrates coverage of topics and issues pertaining to race, class, and gender.